2020
DOI: 10.1111/1462-2920.15000
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postmortem interval based on microbial community sequences and machine learning algorithms

Abstract: Microbes play an essential role in the decomposition process but were poorly understood in their succession and behaviour. Previous researches have shown that microbes show predictable behaviour that starts at death and changes during the decomposition process. Research of such behaviour enhances the understanding of decomposition and benefits estimating the postmortem interval (PMI) in forensic investigations, which is critical but faces multiple challenges. In this study, we combined microbial community char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 61 publications
(97 reference statements)
4
50
1
1
Order By: Relevance
“…Our findings were similar to other work on microbial indicators of PMI estimates showing that while microbes can be used as predictors, the taxonomic groups and level which best predicts PMI are dependent on the surrounding environment [ 64 , 69 ]. Though the limited number of donors and time points in this study did not allow for a robust testing of a continuous interval model, in other studies of postmortem microbiomes, data were able to provide a promising tool for PMI investigation in a variety of habitats and conditions [ 63 , 65 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our findings were similar to other work on microbial indicators of PMI estimates showing that while microbes can be used as predictors, the taxonomic groups and level which best predicts PMI are dependent on the surrounding environment [ 64 , 69 ]. Though the limited number of donors and time points in this study did not allow for a robust testing of a continuous interval model, in other studies of postmortem microbiomes, data were able to provide a promising tool for PMI investigation in a variety of habitats and conditions [ 63 , 65 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 95%
“…According to a previous study, P. mirabilis was able to attract blowflies, which was the reason for the high percentage of V. lutrae 35 . We constructed a model that could explain 87.2% of the variation in the time of death within 1 h. For the corpse the decomposition process, the continuous variables for analysis and particularly fine model developed to estimate the postmortem interval were similar to those in a previous study 14 . The features containing most information for evaluating time of death were selected by best subset selection the genus level, and the features of the poorest model belonged to the phyla.…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the succession of the microbiota during decomposition has applications in forensic science, especially for identifying characteristic bacteria that are closely related to time since death at specific time points. Recent studies have reported bacterial community changes related to animal carcass decomposition 2 , 11 14 . Such studies are starting to determine the universal changes in bacterial communities, including changes in genera and families, identifying the most informative taxonomic microbial communities that change after death transmigration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We constructed a model that could explain 87.2% variation of the time of death within 1 h. Regarding the decomposition process of a corpse as continuous variables for analysis and to develop a particularly ne model to estimate postmortem interval was similar to a previous study [35]. The features contained most information for evaluation death time were selected by Best Subset Selection coming from the genus level and features of the poorest model belong to the phylum.…”
Section: Discussionmentioning
confidence: 99%